The Rise and Fall of the Danish Empire - Bregnsbo, Michael. author. aut Link
XII, 284 p. 26 illus., 21 illus. in color.
Keywords: This book examines the Danish Empire, which for over four hundred years stretched from Northern Norway to Hamburg and was feared by small German principalities to the South. Evolving over time, it has included most of Scandinavia and the North Atlantic, has shifted from a Western orientation under the Vikings to an Eastern one in the Middle Ages, and from a North Sea Empire to a Baltic Empire. From the seventeenth to the early twentieth century, it comprised small overseas colonies in India, Africa and the Caribbean. Exploring the rise and fall of Denmark's Kingdom, from 9 AD to the present, this textbook considers how such vast empires were kept together through ideology and symbols, military force, transport systems and networks of civil servants. The authors demonstrate how the lands under Danish rule included a variety of religious groups, social and economic structures, law systems, and ethnic and linguistic groups. They also consider the economic and ideological benefit of an empire structure in comparison to a nation state. Providing a detailed overview of the long history of the Danish Empire, whilst also confronting current debate and providing novel interpretations, this book offers an original, imperial and multi-territorial perspective on the history of the Danish state, providing essential reading for students of Danish or Scandinavian history and European or Global empires. Michael Bregnsbo is Associate Professor of Early Modern and Modern History at the University of Southern Denmark at Odense. He is a specialist in the history of Danish state formation and Danish absolutism. Kurt Villads Jensen is Professor of Medieval History at Stockholm University in Sweden. Having previously worked at the University of Southern Denmark, he is a specialist in crusading history and cultural encounters in the Middle Ages. His publications include Crusading at the Edge of Europe (2017).